Pan-cancer analysis reveals intratumoral microbial diversity in multiple cancers by amplicon technology - Liu, Xudong; Yao, Yuteng; Xiao, Aoyi; Cao, Dingyan; Zhang, Jingheng; Shi, Yanan; Zhong, Qing; He, Zilong; Wu, Wenming (Frontiers in Cellular and Infection Microbiology, 2025)
Despite numerous studies investigating intratumoral microorganisms and their significant roles in cancer initiation, progression, and treatment efficacy, a systematic understanding of intratumoral microorganisms remains lacking. Herein, we conducted a study using 16S rDNA data on seven types of cancer, comprising a total of 783 samples. It’s worth noting that Pseudomonas, Streptococcus, and Prevotella were found to be shared with the microbial communities of the seven cancers, suggesting that these may be associated with the occurrence and development of cancers. We anticipate establishing a foundation for related research and exploring potential methods for cancer treatment.